The Performance of CURB-65 and PSI for Predicting In-Hospital Mortality of Community-Acquired Pneumonia in Patients with Type 2 Diabetes Compared with the Non-Diabetic Population - Ma CM (Dove Medical Press, 2021)
Chun-Ming Ma,1 Ning Wang,2 Quan-Wei Su,3 Ying Yan,3 Fu-Zai Yin1 1Department of Endocrinology, The First Hospital of Qinhuangdao, Qinhuangdao, Hebei, People’s Republic of China; 2Department of Internal Medicine, Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 3Department of Internal Medicine, Chengde Medical College, Chengde, Hebei, People’s Republic of ChinaCorrespondence: Fu-Zai Yin Email yinfuzai62@163.comObjective: To compare the performance of CURB-65 and Pneumonia Severity Index (PSI) for predicting in-hospital mortality of community-acquired pneumonia (CAP) between patients with and without type 2 diabetes (T2DM).Methods: A retrospective study was conducted on 2365 CAP patients in The First Hospital of Qinhuangdao, China. The primary outcome was in-hospital mortality. The area under curves (AUCs) was used to evaluate the abilities of CRB-65, CURB-65, and PSI class for predicting in-hospital mortality in patients with CAP.Results: Among CAP patients, 127 patients (5.4%) died, 80 patients were without diabetes, and 47 patients had T2DM. In-hospital mortality increased with the risk stratification defined as CURB-65 and PSI class in both non-diabetes and T2DM patients (P< 0.05). The AUCs for predicting in-hospital mortality were 0.728～0.798 in patients without T2DM (CRB-65: 0.728, CURB-65: 0.757 and PSI class: 0.798) and 0.641～0.716 in patients with T2DM (CRB-65: 0.641, CURB-65: 0.677 and PSI class: 0.716)(P< 0.001). The AUC of the PSI class was lower in patients with T2DM than in patients without T2DM (P< 0.05).Conclusion: CURB-65 and PSI class are correlated with in-hospital mortality of CAP in patients with and without T2DM. Compared with non-diabetes patients, the predictive performance of CURB-65 and PSI class decreased in patients with T2DM. A prediction model for evaluating the CAP severity in the T2DM population should be developed by future studies.Keywords: community-acquired pneumonia, CURB-65, pneumonia severity index, mortality, type 2 diabetes